(untitled) (Baghdad Science Journal, 2025)
A total of 96 stool samples were collected from children with bloody diarrhea from two hospitals in Baghdad. All samples were surveyed and examined for the presence of the Escherichia coli O157:H7 and differentiate it from other Non -Sorbitol Fermenting Escherichia coli (NSF E. coli). The Bacterial isolates were identifed by using morphological diagnostic methods, Samples were cultured on liquid enrichment medium, incubated at 37C? for 24 hrs, and then cultured on Cefixime Tellurite -Sorbitol MacConkey Agar (CT- SMAC). 32 non-sorbitol fermenting bacterial isolates were obtained of which 11 were identified as Escherichia coli by using traditional biochemical tests and API20E diagnostic system without differentiation between serotype O157:H7 and other NSF E. coli isolates . Four special biochemical tests were done for serotype O157:H7 differentiation from other NSF bacteria. Only 3 isolates belonging to the serotype O157:H7 were obtained . Latex agglutination test for O157 and H7 showed that the 3 isolates gave positive results with both tests. The Bacterial isolates were identifed by using Multiplex Polymerase Chain Reaction (MPCR) technology for the presence or absence of 4 genes (Stx1, Stx2, hlyA and eaeA) that encode for main virulence factors to diagnose E. coli O157:H7 isolated By using specific primers in MPCR . The result showed that one E. coli O157:H7 isolates contain all 4 genes , other isolates contain 3 genes: Stx2, hlyA & eaeA.